Adaptasi Media Cetak Harian Bhirawa Dalam Menghadapi Konvergensi Media - Alifia Putri Siva; Mitha Andini; Nara Garini Ayuningrum (PT. AHLAL PUBLISHER NUSANTARA, 2025)
The development of digital technology is driving media convergence, requiring print media to adapt to remain relevant amidst the changing media industry landscape. This study aims to analyze Harian Bhirawa's adaptation strategies in addressing media convergence, specifically through its practice of doorstop interview coverage and digital news publication. This study employed a descriptive qualitative approach, with data collection techniques including observation and documentation. The results indicate that Harian Bhirawa integrates print and digital media through a multiplatform publication strategy, where online media serves as a fast and up-to-date information provider, while print media continues to provide more in-depth and contextual reporting. The practice of doorstop coverage is crucial in supporting the speed of publication without neglecting basic journalistic principles. This study provides a theoretical contribution by highlighting micro-journalistic practices in the study of media convergence in local print media.